Meningkatkan Kemampuan Berhitung Permulaan Pada Anak Usia Dini Binaan Rumah Zakat Melalui Video Animasi - Andi Siti Nur Fatimah; Alfiyyah Zhafirah Latif; Nur Tiara Salim; Nurul Apriliana Herli; Nurfitriany Fakhri (Joong-Ki : Jurnal Pengabdian Masyarakat, 2024)
Early childhood education has an important role in developing children's potential from an early age, including in learning to count. psychoeducation reviews efforts to improve early numeracy skills in early childhood through the use of innovative learning media, especially animated videos. The psychoeducation method was used to provide interesting and effective learning for 14 children assisted by Rumah Zakat Makassar. This study used a pretest-posttest approach to evaluate the effectiveness of teaching, with results showing significant improvements in children's understanding and numeracy skills after implementing the animated videos. This implementation proves that fun learning media can increase the motivation and learning outcomes of young children in the context of basic mathematics learning.